Improving the Compliance of Makassar City Government to Public Service Standards: Analysis of Strengths and Weaknesses of the Ombudsman Republic of Indonesia Representative of South Sulawesi - Muhammad Afrisal; Romansyah Sahabuddin; M. Ikhwan Maulana Haeruddin (Universitas Negeri Makassar, 2022)
This study aims to determine the strengths and weaknesses of the Ombudsman Republic of Indonesia Representative of South Sulawesi in improving the Makassar City Government's compliance with public service standards. This is based on the Makassar City Government's compliance assessment which continues to be in the Yellow Zone. Qualitative research methods were chosen to facilitate the presentation of research results. Research data were obtained from interviews, observations, and document studies. The results of the study indicate that the main strength of the Ombudsman of the Republic of Indonesia Representative of South Sulawesi is having the political will of the organizers of public and community services, and the weakness of the human resources is only 17 people is not proportional to the breadth and magnitude of the supervisory task that must be carried out.